Retorika Moderasi Beragama di Kawasan Perbatasan: Penelusuran, Praktek, atau Sebatas Retorika di Aceh Tenggara - Hanifah, Maria (Lembaga Yasin AlSys, 2024)
Rhetoric of Religious Moderation is the art of speaking in implementing a moderate society. Religious moderation illustrates that moderation is not only carried out by Muslims but is carried out by all religions. The aim of this research is to determine the form/practice of religious moderation and its implications within the Ministry of Religion. The research method used is a mixed-method type, concurrent embedded. The analysis used is Miles and Huberman's as well as Quantitative Percentage analysis. The research samples used were the Southeast Aceh Ministry of Religion, KUA, Religious Counselors, FKUB, and the Community. The forms/practices of moderation that are already underway within the Ministry of Religion of Aceh Tenggara include a society that has a national commitment, a society that is non-violent, a society that accepts religious traditions, and a society that is tolerant. Religious moderation which is running in the